Pengaruh Employee Engagement dan Lingkungan Kerja terhadap Kinerja Dosen dengan Organizational Citizenship Behavior sebagai Variabel Intervening - Indra Wijayanto; Muchlis Mas’ud; Ana Sopanah (GEMILANG: Jurnal Manajemen dan Akuntansi, 2025)
This study aims to test and empirically prove the role of employee engagement and the work environment in improving lecturer performance, as well as explore the intervening role of OCB at ITSK dr. Soepraoen Malang. This study uses a quantitative approach with an explanatory research method. The research population of all lecturers was 83 people from 3 faculties. Data collection was carried out through surveys using questionnaires and analyzed using the Partial Least Square (PLS) method using Smart-PLS software. The results of the study show that: (1) employee engagement triggers intrinsic motivation to provide optimal work results. (2) The work environment has an important role in supporting the productivity and effectiveness of lecturers' work. (3) employee engagement not only encourages lecturer productivity, but also strengthens teamwork dynamics through OCB behavior. (4) adequate facilities, a healthy work climate, and positive interpersonal relationships act as catalysts for the emergence of OCB behavior. (5) Lecturers who have a high OCB level will more easily meet the set indicators. (6) the involvement of lecturers and adequate work facilities can improve OCB behavior which has an impact on improving lecturer performance. The practical implications of this study remind us that the success of educational institutions is not only determined by technical factors such as curriculum or facilities, but also by humanistic factors that encourage lecturers to perform better.